Chloro Derivatives of Isomers of a Giant Fullerene C104: C104(234)Cl16/18, C104(812)Cl12/24, and C104(811)Cl28. Issue 20 (20th March 2017) - Jin, Fei; Yang, Shangfeng; Fritz, Maria A.; Kemnitz, Erhard; Troyanov, Sergey I.
Abstract: The chemistry of a giant fullerene, C104, has been extended by the synthesis and structural study of several chloro derivatives of three isolated pentagon rule (IPR) isomers of C104 nos. 234, 812, and 811. In the structure of C104 (234)Cl16/18, two molecules with 16 and 18 attached Cl atoms occupy the same crystallographic site with an occupancy ratio of 61/39. The structures of C104 (812)Cl12 and C104 (812)Cl24 demonstrate substructure relationships of their chlorination patterns with single and double Cl attachments to 12 cage pentagons. The structure of C104 (811)Cl28 is compared with the known C104 (811)Cl24 thus revealing dramatic changes in the chlorination pattern, which occur with relatively small increases in the degree of chlorination. Abstract : Standing on the shoulders of giant fullerenes : New insight into the reactivity of a giant fullerene, C104, was achieved by the structure elucidation of chloro derivatives C104 (234)16/18, C104 (812)Cl12/24, and C104 (811)Cl28 . In C104 (234)Cl16/18 two molecules with 16 and 18 attached Cl atoms are present. The structures of C104 (812)Cl12/24 reveal substructure relationships of the chlorination patterns. The C104 (811)Cl28 molecule has an essentially different chlorination pattern in comparison with C104 (811)Cl24 .